Inhibitory Effect of Imperatorin on the Pharmacokinetics of Diazepam In Vitro and In Vivo - Zhou, Yunfang; Meng, Deru; Chen, Feifei; Wu, Zhengping; Wang, Binglan; Wang, Shuanghu; Geng, Peiwu; Dai, Dapeng; Zhou, Quan; Qiu, Weiwen (Frontiers in Pharmacology, 2020)
Background: Diazepam is a benzodiazepine drug used to treat anxiety, insomnia, and muscle spasms. Imperatorin is a phytochemical isolated from medicinal plants and is widely used in herbal medicine. The aim of this study was to investigate the interactions between imperatorin and diazepam in vitro and in vivo and to provide scientifically based guidance for the safe clinical use of the drug. Methods: In vitro inhibition of imperatorin was assessed by incubating rat liver microsomes with diazepam to determine IC50 values and the type of inhibition. For in vivo assessment, six rats were pretreated with 50 mg/kg imperatorin for two weeks, six were administered saline, and a single dose of 10 mg/kg diazepam was administered orally to both groups 30 min after administration of imperatorin. Results: Imperatorin inhibited the in vitro metabolism of diazepam via the competitive mechanism of CYP450. The IC50 values of imperatorin to nordazepam and temazepam were 1.54 μM and 1.80 μM, respectively. The inhibitory constant values for temazepam and nordazepam were 1.24 μM and 1.29 μM, respectively. Long-term administration of imperatorin significantly increased the AUC(0-12h), AUC(0-∞), and Cmax of diazepam, while Vz/F and CLz/F were decreased significantly (P < 0.05). In turn, the AUC(0-12h), AUC(0-∞), and Cmax of nordazepam and temazepam decreased significantly, and Vz/F and CLz/F increased significantly (P < 0.05). Conclusions: This study demonstrates that imperatorin inhibits the metabolism of diazepam both in vitro and in vivo. These data indicated that more attentions might be paid when taking diazepam together with food or herbs containing IMP, although it still need further investigation in the future.